Perceptions and Beliefs about English Learning in the Community Outreach Unit of a Colombian University - Tiuso Hernandez, Alba Juliana; Bernal Sierra, Eliana Carolina; Coronado Rodriguez, Claudia Camila; Morello Vargas, María Mónica (Colombian Applied Linguistics Journal, 2025)
This paper reports the results of a case study on students’ perceptions and beliefs about language learning at the Community Outreach Unit of Universidad Santo Tomás in Villavicencio, Colombia. The main aim of the study was to analyze the perceptions and beliefs of a group of 17 students regarding English language learning. Data collected through surveys and focus groups was analyzed using the content analysis approach. Results showed that the participants’ beliefs about language learning were linked to effects on their motivation and performance. Additionally, factors such as the demands of globalization and academic requirements were found to play a crucial role in shaping the learners’ affective responses toward the learning experience. Finally, the paper presents the implications from an emotional engagement perspective about the learners’ needs in language learning.